M’sɨt No’kmaq - Riley Olstead; Kim Burnett (Atlantis)
This is a paper about the structural violence of settler colonialism in relation to the limits of the planet. As settler academics, we are involved in this violence. Here, we humbly seek guidance from the land ontology of the Mi’kmaq, reflected in the concept of m’sɨt No’kmaq (All our relations) to understand differently, ourselves, our responsibilities, and our place in ‘a world on fire’ (Rupa and Patel, 2021). Guided by m’sɨt No’kmaq we seek to learn how some of the concepts that we employ in our teaching and research—specifically “trauma” and “climate change” reproduce the core of settler colonialism—the disconnection and elimination of Indigenous peoples from the land (Wildcat et al., 2014, 1). Beyond a conceptual analysis, we also consider “the coloniality of gender” (Lugones 2010, 742) in how the materiality of epistemological violence manifests on the land through state violence directed at Indigenous women, girls, and two-spirit peoples. Our learning throughout the paper shows us how colonial concepts obfuscate settlers’ own relationship to land, which simultaneously undermines the possibility of a generative ethics of settler relationality with Indigenous peoples, and the earth.